SPECIAL PROTECTION OF CHILDREN IN CRIMINAL JUSTICE SYSTEM - Achmad Sulchan (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Children in action to behave and act unlawful could harm himself or society. Law No. 11 Year 2012 on Child Criminal Justice System is designed to protect and nurture children in order to meet a better future, because children must be nurtured in order to obtain their identity to prepare the human being independent and responsible. Thus the very comprehensive in placing the child's position in law, so that the entire law enforcement authorities are involved to participate and solve the problem child, be it the police in conducting investigations and inquiries as well as the Public Prosecutor to prosecute and judge in checking on the court is required to understand the problem of child by following a court education of children, as did the Advocate also demanded to know the problem of child. The case of a child who commits an offense or as victims or witnesses are entitled to all the protections and have exclusive rights to the best interests of the child in the process of condemnation as a last resort. Pursued by way of Diversion and Restorative Justice through, in order to give justice to the victims and the two sides to be able to forgive each other and there was no grudge between them, with the provision of compensation is the emphasis back to its original state and not retaliation. All parties related to the crime of child sit together to resolve the issue amicably and to think about how to overcome the consequences in the future, so will each get justice in accordance justice contained in the precepts and to 2 to 5 of Pancasila is justice with dignity that is humanizing. In the case of criminal case a child should do more in the conference and had the child shouldbe detained, then within 25 days of indictment Public Prosecutor has been delegated to the Juvenile Court and placed in detention Children Special Construction Agency (LPKA). In the course of the trial judges, prosecutors and lawyers are not allowed to wear a toga, but ordinary clothes, while children must be accompanied by parent / guardian and Professional Social Workers. Keywords : Special Protection, Child, crime.